2011
DOI: 10.1128/ec.00308-10
|View full text |Cite
|
Sign up to set email alerts
|

A Second Mitochondrial DNA Primase Is Essential for Cell Growth and Kinetoplast Minicircle DNA Replication in Trypanosoma brucei

Abstract: . These primases are members of the archeoeukaryotic primase superfamily, and each of them contain an RNA recognition motif and a PriCT-2 motif. In Leishmania species, PRI2 proteins are approximately 61 to 66 kDa in size, whereas in Trypanosoma species, PRI2 proteins have additional long amino-terminal extensions. RNA interference (RNAi) of T. brucei PRI2 resulted in the loss of kinetoplast DNA and accumulation of covalently closed free minicircles. Recombinant PRI2 lacking this extension (PRI2⌬NT) primes poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…The majority of kDNA replication proteins studied localize to specific regions surrounding the kDNA, mainly the antipodal sites and the KFZ (17,18,28,29,45). Previously, we demonstrated that TbPOLID is one of three mitochondrial DNA polymerases that are essential for parasite survival and the maintenance of the kDNA network (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of kDNA replication proteins studied localize to specific regions surrounding the kDNA, mainly the antipodal sites and the KFZ (17,18,28,29,45). Previously, we demonstrated that TbPOLID is one of three mitochondrial DNA polymerases that are essential for parasite survival and the maintenance of the kDNA network (6).…”
Section: Resultsmentioning
confidence: 99%
“…RNA editing depends upon guide RNAs (gRNAs) encoded on the heterogeneous population of 5,000 minicircles (1 kb) (49). Therefore, the coordinated replication of both minicircles and maxicircles is essential for mitochondrial physiology and parasite survival.Key features of the kDNA replication mechanism include replication once per cell cycle in near synchrony with nuclear S phase, a topoisomerase II-mediated release and reattachment of minicircles, and a multiplicity of DNA polymerases (six), helicases (six), and primases (two) for kDNA transactions (17,18,22,27,45). Briefly, covalently closed minicircles are released from the network into the kinetoflagellar zone (KFZ), a specialized region between the kDNA disk and the mitochondrial membrane nearest the basal body (bb) (10).…”
mentioning
confidence: 99%
“…We never identified the gene for this enzyme. Jane Hines and Dan Ray (Jane is Dan's wife) subsequently identified genes for two additional mitochondrial primases (57,58), and neither one appeared to be Congjun's enzyme.…”
Section: Proteins Involved In Kdna Replicationmentioning
confidence: 99%
“…A plethora of proteins involved in kDNA replication have been studied in T. brucei, including six helicases (25)(26)(27)40), two DNA ligases (10), two primases (19,20), a topoisomerase IA (40), a topoisomerase II (50), and five DNA polymerases (Pols) (4,7,21,35). The involvement of multiple DNA polymerases in kDNA replication distinguishes this process from replication of other mitochondrial genomes, which depend solely upon DNA polymerase ␥, a family A DNA polymerase.…”
mentioning
confidence: 99%
“…POLIB, POLIC, and POLID lack homologues in mammals, including humans, thus identifying these proteins as potential biological targets for the development of new antitrypanosomal drugs. Analyses of kDNA replication proteins have provided compelling molecular evidence for essential functions in distinct steps of kDNA replication in procyclic form (PF) parasites, a life cycle stage found in its insect vector (4,7,20,26). However, analysis of kDNA replication protein functions in bloodstream form (BF) parasites, the life cycle stage found in the mammalian host and the target for disease intervention (18,37), is an understudied area of trypanosome biology.…”
mentioning
confidence: 99%